An update on risk communication in the Arctic. Issue 1 (31st January 2016) - Krümmel, Eva-Maria; Gilman, Andrew
Abstract : Background: Arctic residents can be exposed to a wide range of contaminants through consumption of traditional (country) foods (i.e. food from wild animals and plants that are hunted, caught or collected locally in the Arctic). Yet these foods provide excellent nutrition, promote social cohesion, meet some spiritual needs for connectedness to the land and water, reinforce cultural ties, are economically important and promote overall good health for many. The risk and benefit balance associated with the consumption of traditional Arctic foods is complicated to communicate and has been referred to as the "Arctic Dilemma". This article gives an update on health risk communication in the Arctic region. It briefly summarizes some research on risk communication methodologies as well as approaches to an evaluation of the outcomes of risk communication initiatives. It provides information on specific initiatives in several Arctic countries, and particularly those that were directed at Indigenous populations. This article also summarizes some international versus local risk communication activities and the complexity of developing and delivering messages designed for different audiences. Finally, the potential application of social media for risk communication and a summary of "best practices" based on published literature and a survey of Inuit in a few Arctic countries are described. Conclusion: Several of the risk communication initiatives portrayed in this article indicate that there is only limited awareness of the outcome of risk communication messages. In some cases, risk communication efforts appear to have been successful, at least when effectiveness is measured in an indirect way, for example, by lower contaminant levels. However, due to missing effectiveness evaluation studies, uncertainty remains as to whether a specific risk communication method was successful and could be clearly linked to behavioural changes that resulted in decreased contaminant exposure.